Effects of a behavioural weight loss intervention in people with serious mental illness: Subgroup analyses from the ACHIEVE trial. Issue 2 (March 2019) - Alexander, Eleanore; McGinty, Emma E.; Wang, Nae-Yuh; Dalcin, Arlene; Jerome, Gerald J.; Miller, Edgar R.; Dickerson, Faith; Charleston, Jeanne; Young, Deborah R.; Gennusa, Joseph V.; Goldsholl, Stacy; Cook, Courtney; et al.
Abstract: Background: Persons with serious mental illnesses (SMI) such as schizophrenia and bipolar disorder have an increased risk of obesity and related chronic diseases and die 10–20 years earlier than the overall population, primarily due to cardiovascular disease. In the ACHIEVE trial, a behavioural weight loss intervention led to clinically significant weight loss in persons with SMI. As the field turns its attention to intervention scale-up, it is important to understand whether the effectiveness of behavioural weight loss interventions for people with SMI, like ACHIEVE, differ for specific subgroups. Methods: This study examined whether the effectiveness of the ACHIEVE intervention differed by participant characteristics (e.g. age, sex, race, psychiatric diagnosis, body mass index) and/or their weight-related attitudes and behaviours (e.g. eating, food preparation, and shopping habits). We used likelihood-based mixed effects models to examine whether the baseline to 18 month effects of the ACHIEVE intervention differed across subgroups. Results: No statistically significant differences were found in the effectiveness of the ACHIEVE intervention across any of the subgroups examined. Conclusions: These findings suggest that the ACHIEVE behavioural weight loss intervention is broadly applicable to the diverse population of individuals with SMI.